2020
DOI: 10.3390/nu12103193
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Histone Acetylation Levels at Th1 and Regulatory Loci after Induction of Food Allergy

Abstract: Immunoglobulin E (IgE)-mediated allergy against cow’s milk protein fractions such as whey is one of the most common food-related allergic disorders of early childhood. Histone acetylation is an important epigenetic mechanism, shown to be involved in the pathogenesis of allergies. However, its role in food allergy remains unknown. IgE-mediated cow’s milk allergy was successfully induced in a mouse model, as demonstrated by acute allergic symptoms, whey-specific IgE in serum, and the activation of mast cells upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…Classical epigenetic mechanisms, including DNA methylation and histone modifications, have been shown to be involved in the development of IgE-mediated food allergies such as CMA [ 171 , 172 , 173 ]. Differences in DNA methylation in different gene pathways have been observed in children who subsequently developed an IgE-mediated food allergy [ 174 ], suggesting their possible role as potential biomarkers.…”
Section: Novel and Future Diagnostic Tests For Non Ige-mediated Fomentioning
confidence: 99%
“…Classical epigenetic mechanisms, including DNA methylation and histone modifications, have been shown to be involved in the development of IgE-mediated food allergies such as CMA [ 171 , 172 , 173 ]. Differences in DNA methylation in different gene pathways have been observed in children who subsequently developed an IgE-mediated food allergy [ 174 ], suggesting their possible role as potential biomarkers.…”
Section: Novel and Future Diagnostic Tests For Non Ige-mediated Fomentioning
confidence: 99%
“…After first exposure and allergic reaction and resolved, histone acetylation of Th2 genes was found lower in the raw milk when compared to processed milk [79]. In another study looking at the effect of cow's milk allergy, a reduced percentage of regulatory T (Treg) and T helper 17 (Th17) cells were prevalent, in parallel to decreased levels of H3 and/or H4 histone acetylation at Treg and Th17 loci [80]. This indicates that activating T cell-related genes can affect the tolerance to milk, and additionally the exposure to raw milk exhibits an allergy-protective effect through the epigenetic modifications of T cells.…”
Section: Histone Acetylation Allows Gene Accessibility To Promote Allergy Reactionmentioning
confidence: 98%
“…This is suggested to be influenced by histone acetylation induced by the dietary substances which later activate the mast cells, especially in acute food allergy reactions that often correlate with severe gastrointestinal issues [81]. This effect is suggested to involve the cell signaling within the mast cells and is related to the activation of Th2 cells [80,82]. In the presence of whey-specific IgE, histone acetylation level is increased to further augment STAT6 gene expression [80].…”
Section: Histone Acetylation Allows Gene Accessibility To Promote Allergy Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study demonstrated that the failure to induce oral tolerance, or the breakdown of oral tolerance as a result of the impaired generation or functioning of the suppressive Tregs, could contribute to food allergy [9]. Newly discovered evidence revealed that the epigenetic modifications, caused by decreased or increased levels of histone acetylation at key Th cell loci, contributed to the allergy to cow's milk protein or the allergy-protective effect of raw milk [10,11]. While it is well known that sodium is an immunomodulator of Th17 cells and Tregs [12], our understanding of the direct effect of sodium on Th2-dependent allergic diseases, such as food allergies, remains scarce.…”
Section: Introductionmentioning
confidence: 99%